Molecular diagnosis of Phytophthora cinnamomi associated with root rot in avocado producing areas of Ecuador - Toapanta Gallegos, Diana Elizabeth; Morillo Velastegui, Luis Eduardo; Viera Arroyo, William Fernando (‎‎Corporación colombiana de investigación agropecuaria - AGROSAVIA, 2018)
One of the most damaging diseases in cultivation of avocado (Persea americana Mill.) is root rot associated with Phytophthora cinnamomi Rands. This disease causes progressive wilt and even death of the tree. The objective of this study was to identify the presence of P. cinnamomi in two productive areas of avocado in Ecuador using the molecular technique PCR-RFLP. Tree root samples were obtained with root rot symptoms in the production areas, from which 10 isolates were morphologically identified with Phytophthora spp. infection. To distinguish among the various Phytophthora species, a molecular analysis was performed using molecular markers in the ITSregion of the ribosomal DNA (rDNA). The ITSdigestion fragment obtained by PCR with the Ta qI enzyme confirmed the presence of Phytophthora cinnamomi in the isolated samples, and its association with root rot in the sampled production areas.